Human Communication with Cyborgs in Experimental Projects of Contemporary Artists and Designers - Anton A. Denikin (Гуманитарный вектор)
The article considers a cyborg as a hybrid of a machine and a biological organism, the functioning of which is carried out through the integration of mechanical, electrical, computational or other artificial components. The transformation of a human into a cyborg allows you to expand or radically transform the possibilities of human communication. The purpose of the article is to find out what are the possibilities of communication between people and cyborgs and how such communications can be carried out. To do this, it is proposed to consider a number of modern art practices and design projects in which experiments on the fusion of a machine and a person are carried out. An analysis of existing cyborg concepts shows that human-machine interactions are increasingly being analyzed not from a human perspective but in the context of their technological hybridity. Instead of talking about technologies as extensions of the human body, a discourse is being formed that articulates the initially prosthetic nature of human identity, where human identity is always conditioned by the interactions and contacts with technology themselves. At the same time, the creative experiments cited in the article, although they demonstrate a revision of some prerequisites of the theory of communication (concepts of subject, knowledge, understanding, meaning, freedom of action), they are addressed in one way or another to man and human communication, which is confirmed by the works of N. Harbisson, M. Ribas, J. Dekney, P. Lopez, Stelark’s performances and other cyber artists and designers. For all the originality and provocativeness of the ideas, the projects they organize retain the need for a human subject capable of assessing what is happening from the outside, asking artistic and ethical questions, searching and finding answers to them in real practice.